PENGARUH BRAND EXPERIENCE DAN BRAND IMAGE TERHADAP WILLINGNESS TO PAY A PRICE PREMIUM DENGAN BRAND LOVE SEBAGAI VARIABEL INTERVENING (Studi Pada Pemilik Mobil Merek Honda HRV di Samarinda) - Mega Aulianda (Jurnal Riset Entrepreneurship, 2020)
This study aims to determine the effect of brand experience and brand image on the willingness to pay a premium price for Honda HRV products in Samarinda mediated by brand love variable. Data collection in this study was carried out by using an instrument in the form of a set of questionnaires distributed to 95 owners of Honda HRV cars within Samarinda area. Data from the questionnaires were subsequently analyzed using SEM-PLS analysis techniques with the help of the smartpls version 3.9 program. Based on the results of the analysis in this study, it is obtained that directly, brand experience, brand image and brand love have positive and significant effects on the willingness to pay a premium price. The results of the analysis also showed that brand experience and brand image have positive and significant effects on brand love; and brand love proved to be able to mediate the indirect effect of brand experience and brand image on the willingness to pay a premium price for Honda HRV product consumers. The findings of this study indicate that the better the brand image of Honda HRV and the higher brand experience of Honda HRV consumers, the higher the brand love of consumers which will further increase the desire of consumers to buy HRV products even at high prices. Theoretically, the findings of this study are in accordance with some previous researches and existing theories. Practically the findings of this research are expected to be a scientific reference for business people in automotive sector, especially in Samarinda to build brands effectively and efficiently. Keywords : Brand Experience, Brand Image, Willingness To Pay a Price Premium, Brand Love